Las epidemias de cólera en Córdoba a través del periodismo: la oferta de productos preservativos y curativos durante la epidemia de 1867-1868 Cholera epidemics in Córdoba as seen through the press: the supply of preventive and curative products during the 1867-68 epidemic - Adrián Carbonetti; María Laura Rodríguez (História, Ciências, Saúde: Manguinhos, 2007)
La enfermedad es un momento de crisis tanto individual como social. La cercanía de la muerte debido a la dolencia genera en las sociedades estrategias para evadirla o curarla. Las epidemias y especialmente las de cólera tuvieron una impronta muy fuerte en la sociedad argentina y especialmente en la cordobesa ya que la primera de ellas fue devastadora en términos demográficos y sociales. En este artículo pretendemos analizar el ofrecimiento de productos, que se publicaba en la prensa escrita en la primer epidemia del año 1867/68. Partimos de la hipótesis de que los productos que se ofrecían desarrollaban un comercio de carácter suntuario que no eran objeto de transacciones comerciales habitualmente por la población en momentos no epidémicos y que a su vez estaban dirigidos hacia los sectores de mayor nivel adquisitivo. Throughout human history, disease has always represented a moment of crisis for individuals and societies. When death brought by disease hangs heavy over societies, they are led to develop strategies to prevent and cure it. Epidemics, especially cholera epidemics, have had a strong impact on Argentine society and especially on Córdoba residents, because the first cholera outbreak was demographically and socially highly devastating. In this article we analyze the supply of products advertised in the press (the only media available at the time) during the first epidemic, which broke out in 1867-8. Our hypothesis is that the products available, which we believe were consumed by some groups in society, led to a sumptuary trade that was not common among the population when there were no epidemics. At times of epidemics, these products were directed towards more affluent groups. We also believe that the supply of such products changed as their trade increased.